A review of the Romanian Halticoptera Spinola (Hymenoptera: Chalcidoidea, Pteromalidae), with description of three new species - Mitroiu, Mircea-Dan (Zootaxa, 2005)
The Romanian species of Halticoptera Spinola (Hymenoptera: Chalcidoidea, Pteromalidae) are reviewed. The species Halticoptera askewi, H. andriescui and H. semireticulata  are described as new. Halticoptera dimidiata (Förster) and H. patellana (Dalman) are new to Romania. A key to the eleven Romanian species of Halticoptera is given.